The power of many. (Economist, 2011)
The article looks at personalized computing using mobile electronic devices. How the devices are personalized to their users through portability, individual cases, and mobile device applications is discussed. Also noted are companies that produce these gadgets including Apple, Samsung, and HTC. Cloud computing software Dropbox and video chat software Skype are reviewed.